How to prepare secondary students for high-stake tests - Association for Supervision and Curriculum Development (Alexandria, VA : ASCD, 2001)
Shows how teachers are helping high school students by: teaming with fellow teachers to review and align curriculum to required standards; providing students with opportunities to review and practice taking cumulative tests; dividing content and skills into manageable segments; and having a process in place for those students who may need additional help
Title from title screen
Keywords: Test-taking skills -- United States; High schools -- United States -- Examinations; Educational tests and measurements -- United States